EFIKASI DIRI SEBAGAI INTERNAL BUFFER TERHADAP BURNOUT - Lailani, Fereshti (TALENTA, 2015)
ABSTRACTBurnoutÂ  isÂ  aÂ  psychologicalÂ  responseÂ  toÂ  workÂ  stressÂ  thatÂ  isÂ  characterizedÂ  by emotionalÂ  exhaustion,Â  depersonalization,Â  andÂ  reducedÂ  feelingÂ  ofÂ  personal accomplishment (low personal accomplishment). This paper intends to explain one of the variables that the results of some studies have shown to have a role in burnout , which is selfÂ  âÂ  efficacy.Â  Self-efficacy is the beliefs about oneâs ability to accomplish specific tasks. Self-efficacyÂ  affectsÂ  employeesâÂ  levelÂ  toÂ  effortÂ  andÂ  persistenceÂ  whenÂ  learningÂ  difficult tasks.Â  AÂ  numberÂ  ofÂ  researchÂ  studyÂ  wasÂ  foundÂ  thatÂ  perceivedÂ  senseÂ  ofÂ  self-efficacyÂ  was correlatedÂ  withÂ  perceivedÂ  burnoutÂ  :Â  theÂ  lowerÂ  theÂ  senseÂ  ofÂ  self-efficacyÂ  moreÂ  was perceived burnout. The individuals having low self-efficacy have not much control of their behavior and actions. They are more vulnerable to burnout.Key words :Burnout, Self-Efficacy